PENERAPAN PENDEKATAN RME (Realistic Mathematics Education) UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VI SDN KERTOSARI 02 MADIUN PADA MATERI PERKALIAN PECAHAN - Pramitasari, Diana; Tryanasari, Dewi; Juhariyani, Ria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research conducted was motivated by the low mathematical problem-solving skills of sixth-grade students at SDN Kertosari 02 Madiun. The sixth-grade students had difficulty understanding the questions and translating word problems about fraction multiplication into mathematical sentences, thus failing to solve the problems. The type of research conducted was Classroom Action Research (PTK), which consisted of two cycles. Each cycle was carried out in two meetings. The research subjects were 19 sixth-grade students at SDN Kertosari 02 Madiun. This research was conducted in the mathematics subject on the topic of fraction multiplication. The research aimed to determine the implementation of planning, the execution of teaching by teachers and students, and the learning outcomes using the RME approach to improve the mathematical problem-solving skills of sixth-grade students. Data in this research were collected through observation, interviews, and tests. Based on the results of data analysis, the implementation of the learning planning stages increased by 11% from cycle 1 to cycle 2. The implementation of learning using the RME approach by teachers increased by 11%, while the implementation of learning using the RME approach by students increased by 10%. The application of the RME approach can improve the mathematical problem-solving skills of sixth-grade students at SDN Kertosari 02 in the topic of fraction multiplication. The classical mathematical problem-solving skills in the pre-cycle were 63%, in cycle 1 were 76%, and in cycle 2 were 86%, which falls into the very good category.